Modified polyethylene glycol hydrogels for growth factor delivery and controlled tissue invasion - Gustafsson, Carla Astrid (Division of General Surgery, 2020)
The prevalence of cardiovascular disease and myocardial infarction-induced heart failure has risen significantly over recent years, emphasising the need for new, effective therapeutic strategies. A promising alternative approach is the cardiac delivery of potentially cardioprotective and regenerative growth factors from biomaterial scaffolds. One hydrogel system that has promise in this area is an injectable enzymatically degradable polyethylene glycol (PEG) hydrogel. Two modifications aimed at further optimising this system as a regenerative medicine scaffold were explored. Firstly, the covalent addition of heparin into the PEG backbone was assessed for its ability to stimulate angiogenesis by assessing the controlled release of basic fibroblast growth factor (bFGF), vascular endothelial growth factor (VEGF) and placental growth factor 2 (PlGF-2), and also assaying endothelial cell sprouting in an in vitro 3D spheroid angiogenesis assay. The second modification involved overlaying an increasingly hydrolytic degradability on top of the enzymatically degradable background of the hydrogel. The potential of this modification to regulate the rate of hydrogel replacement by invading tissue was assessed in the 3D spheroid assay and a subcutaneous implant study in a rat model. The covalent coupling of heparin was found to substantially increase the rate of release of bFGF, VEGF and PlGF-2 over 20 days by 23%, 42% and 19%, respectively, relative to nonheparinised PEG hydrogels (p<0.01). A 3D spheroid-based angiogenesis assay was modified for use in quantifying endothelial cell sprouting in PEG hydrogels. bFGF and VEGF were shown to elicit a significant increase (2.3 – 2.4-fold increase) in average cumulative sprout lengths relative to that seen in the control spheroids (p<0.01). However, PlGF-2 did not stimulate a significant response (1.4-fold increase, p=NS). In follow up studies with heparinised hydrogels, it was found that the 3D angiogenesis was not rigorously established and ways forward are discussed. Enzymatically degradable PEG hydrogels that retained their enzymatic degradability with increasing levels of potential for hydrolysis were formed by increasing the proportion of PEGacrylate (PEG-Ac) and correspondingly decreasing the portion of PEG-vinyl sulfone (PEG-VS) monomers. PEG-Ac forms hydrolytically unstable bonds with the peptide crosslinker whilst 4 PEG-VS forms stable linkages. This approach was shown through swelling studies to be capable of generating a range of hydrolytic degradation rates. Sprouting of endothelial cells from PEG hydrogel embedded spheroids was shown to increase as the PEG-AC concentration increased. Importantly, the rate of tissue invasion in vivo was also shown to be positively correlated with the PEG-Ac concentration. The increased utility of these hydrogels to act as delivery vehicles for therapeutic agents, through covalent coupling of heparin, is promising for their use as regenerative medicine scaffolds. Additionally, so is the ability to finely tune tissue invasion by manipulating their hydrolytic degradability.